Genre and stylistic features of Nurtore Zhusip’s journalism - Ashirbekova Г.Ш.; Murat А.М. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
This article analyzes creative skills, and in general the works of Nurtore Zhusip. The article highlights current articles of the publicist, his creative laboratory is studied. In the course of writing articles, there has been identified topical problems of society based on his journalistic works. Special attention has been paid to topical issues that the publicist raises in his works. In the article you can also get acquainted with the thoughts of the luminaries of journalism, who followed and were inspired by the work of Nurtore Zhusip. Using the thoughts and analysis of scientists in the field of journalism, the creative personality of the publicist is highlighted. In the course of studying and researching there is revealed creative heritage of the publicist, the main idea of his works